Analytical Model of Radio-Frequency Ion Thruster. (2017) - Kanev, Stepan V.; Khartov, Sergey A.; Nigmatzyanov, Vladislav V.
Abstract: The radio-frequency ion thruster (RIT) is a gridded ion accelerator which is used as an alternating electro-magnetic field for plasma production. It is suggested to use the 0-D analytical model based on energy and particles balance equations for RIT integral parameters estimation as well as for quick analysis of the influence of RIT design modification on thruster performance improvement. The numerical results of 0-D model (geometry of the discharge chamber, input power, ion current) can be used as the first assumption for more complicated models (1-D or 2-D). The calculations are verified by experimental data. Such analysis is very helpful for an experimental research of the thruster. It gives the possibility to reduce the amount of hours of the experimental work, and consequently the cost of the experiment.